Bridge of Faith: Aim4Peace Community-Based Violence Prevention Project, Kansas City, Missouri, 2014-2017 - Watson-Thompson, Jomella ([Verlag nicht ermittelbar], 2022)
This study followed the outcomes of the Bridge of Faith program. Bridge of Faith is an expansion project based on efforts of the Aim4Peace Violence Prevention Program, serving youth 13-24 years of age living in a prioritized area of Kansas City, Missouri. Bridge of Faith created goals and objectives that strategically address a continuum from response to violence exposure, intervention for violence survivors, and preventing of violence exposure. Activities were designed to target a reduction in risk factors and improvement in resiliency factors associated with the use of violence, as well as improve access to care and quality of services for those who are survivors of violence to reduce the probability of violence and exposure to others in the future. The overall purpose was to improve the health, social, and economic outcomes for youth and families who have been exposed to trauma and/or violence and prevent further violence from occurring. The project will facilitate these outcomes in specific goals and objectives to expand access to evidence-based programs and services for youth survivors through a new platform for collaborating agencies to link survivors of violence to additional wrap around services, and enhance the performance of service agencies through training, strengthening knowledge and skill development to ensure quality, trauma-informed, and culturally competent care. This study on the Bridge of Faith Project was split into two datasets, Participant Survey Data and Police Data. Individuals were the unit of analysis measured in the Participant Survey Data, and criminal acts were the unit of analysis measured in the Police Data. Participant Survey Data contains 22 variables and 12 cases. Police Data contains 26 variables and 9 cases.